Prototipagem com modelagem e impressão 3D de braço robótico para deposição de filmes finos pela técnica de spray-pirólise - Bezerra, Daniel Alves (2023)
The strong presence of automation in industrial processes brings an pportunity to improve and optimize traditionally manual manufacturing processes, more specifically laboratory ones. By means of equipment that perform pre ordered and repetitive tasks, it is possible to reduce the occurrence of human errors and contribute to the safety of operators, avoiding their contact with products that are harmful to health. Currently there are research for the development of cheaper photovoltaic systems, among them, the Grätzel cell, also known as photochemical solar cell, or dye sensitized nanocrystalline solar cell (CSNS). They have some of its components manufactured through a process carried out in a traditional manual way, known as Spray Pyrolysis.Pyrolysis. The purpose of this work is the automation of the spraying procedure used in this process so that the repetitive movements performed by the operator, usually manually, are performed by a robotic arm, which can be controlled by a smartphone application or through a device composed of potentiometers developed for the project. Initially, a robotic arm configuration and its characteristics were chosen, and the articulated model was selected. A programming code was developed in the C/C++ language, using the Arduino prototyping platform, to allow the arm to function. The prototype parts were developed in a 3d simulation software and manufactured using 3d printing. The electronic system of the robotic arm was developed The results show that the prototype receives the operator's commands and executes them repeatedly, presenting a variation of 6% between the simulated movements and the movements executed when a command is carried out.